Pemberdayaan Masyarakat Melalui Edukasi Dan Pelatihan Tentang Pembuatan Tanaman Hidroponik System Wick Dengan Memanfaatkan Bahan Bekas Melalui Program KZW (Kampung Zero Waste ) Di Rw 02 Gunungsari Surabaya - Deavita Lusi Rahmawati; Ni Made Ida Pratiwi; Febby Rahmatullah Machrusin (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
Community empowerment is a crucial effort in improving the well-being and environmental sustainability, especially in the Rw 02 Gunungsari area. In the current modern era, waste management and environmental conservation have become central issues faced by the community. Therefore, creative and innovative steps are needed tot address these problems. The surabaya city goverment, particularly the environmental agency, has initiated the MBKM KZW (Zero Waste Village) program involving the entire community of Rw 02 Gunungsari and students from the 17 August 1945 University of Surabaya in an effort to reduce waste and preserve the environment. One approach to achieve this is through education and training on the creation of a wick hydroponick system using recycled materials duet o limited space. The goal of this education and trainning is to enhance the community’s knowledge of the latest agricultural technology and reduce waste by utilizing recycled materials to create a self-sufficient and sustainable environment.